16.7k views
1 vote
4. Apply DeMorgan's theorems to simplify the following Boolean expression.

F (A, B, C) = A (A + BC) + A (B+C)

User Pierre F
by
5.8k points

1 Answer

7 votes

Answer:

Step-by-step explanation:

the Boolean expression, the simpler the resulting logic. BABA∙. = + ... DeMorgan's Theorem #1 ... BA∙. A. B. A. B. A. B. BA. +. B. 0. 0. 0. 1. BA∙ BA∙. A. B. 0. 0. 1. 1. 1. A. B. A. B. BA. +. 0. 0 ... Y X . 10A). +. = +. ∙. = ∙. Commutative. Law. X 0 X 5). 0 X X 4). X X X 3). = +. = ... Simplify the following Boolean expression and note the.

User Sgibly
by
4.7k points